Mechanics of materials and structures - Voyiadjis, G. Z.; Bank, Lawrence Colin 1956-; Jacobs, Laurence J. (Studies in applied mechanics, 1994)
"Presented at the Bieniek Symposium on Mechanics of Materials and Structures in conjunction with the MEET'N '93, First SES-ASME-ASCE Joint Meeting on Mechanics, at the University of Virginia, Charlottesville, Virginia, June 6-9, 1993"--P. [v].